ANALYSIS OF ADAPTIVE PHYSICAL EDUCATION LEARNING IN THE COVID-19 PANDEMIC PERIOD AT KETAPANG DISTRICT - Rahmat, Ade (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
Covid-19 has a real impact on the learning activities of Physical Education subject teachers in the Ketapang Regency. This study aims to describe the circumstances or conditions regarding the implementation of physical education learning for students with special needs (Adaptive Physical Education) during the Covid-19 pandemic in the Ketapang Regency, West Kalimantan Province. This research is research with a quantitative approach with a survey method. The sample in this study were physical education teachers in Ketapang Regency, totaling 14 teachers from 14 elementary schools from all physical education teachers in Ketapang Regency who carried out Adaptive learning. The research instrument used in this study was an online questionnaire using a validated google formula. The data analysis used in this research is descriptive quantitative research data analysis. Based on the results of the study, there were 14 elementary schools from 7 districts in Ketapang Regency which implemented adaptive physical education during the pandemic. 92.86% of teachers have been guided by the subject curriculum, 60.71% of respondents thought that the 2013 curriculum, 80.36% of Physical Education teachers made Prota instruments, while 73.21% had made Promes, and 76.79%. Making RPP with format 1. It is concluded that Adaptive Physical Education Learning in Ketapang Regency has been implemented online, where there are still obstacles, namely difficulties with an internet connection, low adaptive physical education learning assistance by parents, and the lack of ability to modify learning methods during the Covid-pandemic. So that learning becomes less effective.